Determinants of Customers’ Adoption of Mobile Banking in Nepalese Commercial Banks - Prasad Aryal, Narayan; Bahadur Hamal, Janga; Kumar Singh, Gobind (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: This paper assesses the determinants of customers’ adoption of mobile banking in Nepal, employing the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. Design/methodology/approach: The philosophy of positivism guided this study, adopted a quantitative approach, and applied deductive reasoning. The research utilized an explanatory research design to investigate the relationships of cause and effect between the variables. A survey was carried out among 193 participants from Nepalese commercial banks to collect data. The study’s population encompasses a diverse array of customers utilizing mobile banking services across commercial banks, with the sample comprising students and teachers associated with KUSOM. The study employed purposive sampling to ensure a robust and diverse sample, drawing from the most accessible segment of the population. Findings: This study has identified several factors that significantly influence customer adoption behaviors, including perceived usefulness, perceived ease of use, perceived risk, service quality, trust, awareness, and perceived cost. The result exhibited that perceived usefulness, ease of use, service quality, trust, and perceived cost positively and significantly affect the adoption of mobile banking. In contrast, perceived risk and perceived cost demonstrate negative impacts, while awareness shows insignificant impact on adoption of mobile banking. Conclusion: The study reveals that Nepal’s mobile banking adoption faces challenges like distrust, perceived risks, and insufficient awareness, despite its potential for convenience and efficiency, emphasizing the need for enhanced communication, security, and user guidance. Implications: This research provides actionable insights for banking institutions aiming to improve their mobile banking services and better serve the evolving needs of their customers in Nepal. JEL Classification: G21, O33, D83, M15